The Effect of Online Communication and Use of Information Systems on Audit Quality - Rendi Kusuma Natita; Neni Maryani (Research Collaboration Community (RCC), 2023)
During the Covid-19 pandemic it became a challenge for the Public Accounting Firm to carry out audit procedures. During the Covid-19 pandemic, physical meetings or communication between auditors or public accountants and a company's clients were limited, so these meetings, which were generally held face-to-face, became online meetings. The main obstacle for auditors or public accountants during the Covid-19 pandemic is that the audit procedures that must be carried out for the 2020 financial statements will be different from the previous year. In general, audit engagements or communication with clients to obtain audit evidence is carried out face-to-face, but to reduce the spread of the Covid-19 virus, such communication is carried out online. Of course, these communication issues must still be guided by Auditing Standard 260 regarding communication with those charged with governance. This study aims to determine the effect of online audit communication and the use of information systems on audit quality. This research is research with the aim of testing the hypothesis. Studies that engage in hypothesis testing usually explain the nature of a particular relationship or determine the independence of two or more factors in a situation. This study uses an explanatory method where the researcher wants to find the cause of one or more problems. This study aims to determine the effect of online audit communication and the use of information systems on audit quality. This research is research with the aim of testing the hypothesis. Studies that engage in hypothesis testing usually explain the nature of a particular relationship or determine the independence of two or more factors in a situation. This study uses an explanatory method where the researcher wants to find the cause of one or more problems. This study aims to determine the effect of online audit communication and the use of information systems on audit quality. This research is research with the aim of testing the hypothesis. Studies that engage in hypothesis testing usually explain the nature of a particular relationship or determine the independence of two or more factors in a situation. This study uses an explanatory method where the researcher wants to find the cause of one or more problems.